Essays on taxation and social protection in developing countries - Jouste, Maria (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
This doctoral dissertation investigates how tax administration and tax and social protection policies impact citizens’ income and tax authorities’ revenue collection in the developing world. Two of the essays use impact evaluation methods and administrative tax data, whereas the third essay employs microsimulation modelling and survey data. The first essay studies how a taxpayer register campaign and a simpler electronic tax filing form impact the number of taxpayers and tax revenues. We use the Ugandan administrative data from 2012–18 in a staggered and standard differencein-difference analysis. We find that both reforms significantly increased the number of presumptive taxpayers and tax revenues. The reforms complement each other, and the taxpayer register campaign was cost-effective. The second essay studies the impact of a large personal income tax reform in 2012 on employees’ income and tax revenues in Uganda. We use the difference-indifference approach and the Ugandan tax register data from 2010–15. Our analysis focuses on the high-income earners because they faced the largest increase in the marginal tax rate. We find that the elasticity of taxable income is high compared to developed countries. Revenue implications of the reform are positive even though behavioural responses are significant. The third essay investigates the effects of hypothetical universal pension reforms on poverty and inequality in Ecuador, Ghana, Tanzania, and South Africa and calculates the reforms’ cost implications. We use tax-benefit microsimulation modelling and nationally representative household survey data to analyse the impacts of three different universal pension scenarios. We find that universal pensions reduced poverty and inequality in Ghana and Tanzania. In South Africa, universal pensions have a limited impact on poverty and inequality compared to the existing old-age pension, which covers most poor elderly. In Ecuador, the effect of universal pensions depends on the existing means-tested pensions. When the universal pension was given as a top-up scheme, it reduced poverty and inequality because the existing pension did not reach all vulnerable elderly. In all countries, the cost implications are substantial.

Esseitä verotuksesta ja sosiaalituista kehittyvissä maissa Tämä kokoomaväitöskirja tutkii kuinka verohallinto, verotus ja sosiaalituet vaikuttavat kansalaisten toimeentuloon ja verotuloihin kehittyvissä maissa. Väitöskirjan kaksi esseetä käyttävät vaikutusanalysointia ja hallinnollisia veroaineistoja, kun taas yksi essee hyödyntää mikrosimulointimallinnusta ja kyselyaineistoja. Ensimmäinen essee tutkii kuinka veronmaksajien rekisteröintikampanja ja yksinkertaisempi verolomake pienille yrityksille ovat vaikuttaneet veronmaksajien määrään ja verotuloihin. Käytämme ugandalaista veroaineistoa vuosilta 2012–18 ja hyödynnämme porrastettua ja tavanomaista difference-in-differences –menetelmää. Tutkimuksen tuloksena on, että molemmat reformit lisäävät merkittävästi veronmaksajien määrää ja ja verotuloja. Lisäksi reformeilla on yhteisvaikutus ja veronmaksajien rekisteröintikampanja on kustannustehokas. Toinen essee tutkii kuinka henkilön tuloverotuksen muutos vuonna 2012 vaikutti työntekijöiden tuloihin ja verotuloihin Ugandassa. Käytämme difference-indifferences –menetelmää ja ugandalaista veroaineistoa vuosilta 2010–15. Keskitymme analyysissamme eniten ansaitseviin palkansaajiin, koska heidän marginaaliveroasteensa kasvoi merkittävästi. Tutkimuksemme osoittaa, että verotulojen joustavuus on korkea verratuna kehittyneisiin maihin. Reformi vaikutti positiivisesti verotuloihin, vaikka käyttäytymisvaikutukset ovat merkittäviä. Kolmas essee analysoi kuinka hypoteettiset universaalit eläkereformit vaikuttavat köyhyyteen ja epätasa-arvoon Ecuadorissa, Ghanassa, Tansaniassa ja Etelä- Afrikassa. Lisäksi laskemme reformien kustannukset. Hyödynnämme mikrosimulointimallinnusta ja kansallisesti edustavaa kotitalouksien kyselyaineistoa analysoidaksemme kolmen erilaisen universaalin eläkereformin vaikutuksia. Tutkimuksemme osoittaa, että universaalit eläkkeet vähentävät köyhyyttä ja epätasa-arvoa Ghanassa ja Tansaniassa. Etelä-Afrikassa universaaleilla eläkkeillä on rajoittunut vaikutus köyhyyteen ja epätasa-arvoon verratuna olemassa oleviin eläkkeisiin, jotka tavoittavat suurimman osan köyhistä vanhuksista. Ecuadorissa universaalin eläkkeen vaikutus riippuu olemassa olevista tarveharkintaisista eläkkeistä. Kun universaali eläke annetaan lisätulona, se vähentää köyhyyttä ja epätasa-arvoa, koska olemassa olevat eläkkeet eivät tavoita kaikkia haavoittuvassa asemassa olevia vanhuksia. Kaikissa maissa, eläkereformien kustannukset ovat huomattavat.